The City as a License. Implications of Blockchain and Distributed Ledgers for Urban Governance - Gloerich, Inte; De Waal, Martijn; Ferri, Gabriele; Cila, Nazli; Karpinski, Tara (Frontiers in Sustainable Cities, 2020)
Distributed ledger technologies (DLTs) such as blockchain have in recent years been presented as a new general-purpose technology that could underlie many aspects of social and economic life, including civics and urban governance. In an urban context, over the past few years, a number of actors have started to explore the application of distributed ledgers in amongst others smart city services as well as in blockchain for good and urban commons-projects. DLTs could become the administrative backbones of such projects, as the technology can be set-up as an administration, management and allocation tool for urban resources. With the addition of smart contracts, DLTs can further automate the processing of data and execution of decisions in urban resource management through algorithmic governance. This means that the technological set-up and design of such DLT based systems could have large implications for the ways urban resources are governed. Positive contributions are expected to (local) democracy, transparent governance, decentralization, and citizen empowerment. We argue that to fully scrutinize the implications for urban governance, a critical analysis of distributed ledger technologies is necessary. In this contribution, we explore the lens of 'the city as a licence' for such a critical analysis. Through this lens, the city is framed as a ‘rights-management-system’, operated through DLT technology. Building upon a right to the city-discourses (Lefebvre et al. 1996), such an approach allows to ask important questions about the implications of DLTs for the democratic governance of cities in an open, inclusive urban culture. Through a technological exploration combined with a speculative approach, and guided by our interest in the rights management and agency that blockchains are claimed to provide to their users, we trace six important issues: quantification; blockchain as a normative apparatus; the complicated relationship between transparency and accountability; the centralizing forces that act on blockchains; the degrees to which algorithmic rules can embed democratic law-making and enforcing; and finally, the limits of blockchain's trustlessness.